2016
DOI: 10.1080/10773525.2016.1168588
|View full text |Cite
|
Sign up to set email alerts
|

Work accident victims: a comparison between non-standard and standard workers in Belgium

Abstract: Background: The fast growth of non-standard employment in developed countries highlights the importance of studying the influence of contract type on worker's safety and health. Objective: The main purpose of our study is to investigate whether non-standard workers are more injured than standard workers or not. Additionally, other risk factors for occupational accidents are investigated. Methods: Data from the Belgian surveys on work ability in 2009 and 2011 are used. During their annual occupational health ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Using our simple taxonomy and proposed mechanisms researchers can examine distinct contractual dimensions of work arrangements to advance research on the health implications of non-standard work. For example, perhaps the consistent finding of increased injury risk among temporary staffing agency workers [e.g., ( 6 )] and more mixed results among temporary direct hires [e.g., ( 51 )] can be explained by the indirect nature of the staffing agency model. We can hypothesize that a diffusion of responsibility for worker safety between the multiple involved employers mediates health outcomes for temporary staffing agency workers in ways that may not be applicable to temporary direct hires.…”
Section: Discussionmentioning
confidence: 99%
“…Using our simple taxonomy and proposed mechanisms researchers can examine distinct contractual dimensions of work arrangements to advance research on the health implications of non-standard work. For example, perhaps the consistent finding of increased injury risk among temporary staffing agency workers [e.g., ( 6 )] and more mixed results among temporary direct hires [e.g., ( 51 )] can be explained by the indirect nature of the staffing agency model. We can hypothesize that a diffusion of responsibility for worker safety between the multiple involved employers mediates health outcomes for temporary staffing agency workers in ways that may not be applicable to temporary direct hires.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies investigated the relation between temporary contracts and risk of injuries. One of these found a statistically significant positive association (14), while four studies showed inconclusive results or negative associations (20,(24)(25)(26). Four studies on part-time or casual work suggested negative or no relation to occupational injuries (18,19,25).…”
Section: Dimensions Of Precarious Employment Studied and Their Associmentioning
confidence: 99%
“…In addition, as shown by other studies, the poor hygiene standards and inadequate risk as-sessment are associated with increased injury risk (15)(16)(17)(18)(19). An interesting observation emerges from a study conducted in Belgium (20): the economic crisis and the instability of the labor market have recently resulted in the introduction of new forms of contractual agreements (atypical contracts); atypical workers frequently appear to be neither sufficiently qualified nor adequately trained and informed, which makes these workers more vulnerable to safety risks. It is in this context that 1,886 atypical workers were interviewed between 2009 and 2011 in order to assess the existence of a statistically significant difference in the rate of occupational accidents observed as compared to workers with standard employment contracts.…”
mentioning
confidence: 64%